2015
DOI: 10.21769/bioprotoc.1563
|View full text |Cite
|
Sign up to set email alerts
|

Adoptive Transfer of Memory B Cells

Abstract: The adoptive transfer of antigen-specific B cells into mice that cannot recognize that specific antigen has two main advantages. The first is determining exactly when the B cells were transferred and exposed to antigen. The second is that all B cells that can bind that antigen are the ones that were transferred; no new antigen-specific B cells will emerge from the bone marrow. Thus all B cells that were exposed to the antigen and still alive after at least 4 weeks (8 weeks or more is ideal), are memory B cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…(1x10 7 cells/mouse) into NSG mice 4 weeks post PFFs injection. The optimal number of T and B cells for adoptive transfer ranges from 1x10 6 -1x10 7 cells/mouse [41][42][43][44][45][46]. Purification of T and B cells from total splenocytes was carried out by negative selection using Dynabeads untouched mouse T cells and Dynabeads untouched CD43 B cells isolation kits according to the manufacturer's instruction (Invitrogen).…”
Section: Adoptive Transfermentioning
confidence: 99%
“…(1x10 7 cells/mouse) into NSG mice 4 weeks post PFFs injection. The optimal number of T and B cells for adoptive transfer ranges from 1x10 6 -1x10 7 cells/mouse [41][42][43][44][45][46]. Purification of T and B cells from total splenocytes was carried out by negative selection using Dynabeads untouched mouse T cells and Dynabeads untouched CD43 B cells isolation kits according to the manufacturer's instruction (Invitrogen).…”
Section: Adoptive Transfermentioning
confidence: 99%
“…To study antigen-specific ABCs after immunization, we transferred PfCSP-specific Igh g2A10 cells ( 37 ) to MD4 recipients and immunized with Plasmodium berghei –PfCSP sporozoites (PfCSP-SPZ) that express the PfCSP in place of the endogenous P. berghei CSP protein (PbCSP) ( 38 ). The use of the MD4 recipient Ig-transgenic mice that express an irrelevant BCR (hen egg lysozyme) is an established approach for the study of rare memory cell populations ( 39 ). Additionally, we confirmed that the Igh g2A10 B cell did not respond to noncognate antigen or SPZs under such settings (fig.…”
Section: Resultsmentioning
confidence: 99%
“…To assess this we transferred PfCSP-specific Igh g2A10 cells (28) to MD4 recipients and immunized with P. berghei -PfCSP sporozoites (PfCSP-SPZ) that express PfCSP in place of the endogenous P. berghei CSP protein (29). The use of recipient Ig-transgenic mice which express an irrelevant BCR - in this case specific for hen egg lysozyme - is an established approach for the study of rare memory cell populations (30). Immune responses were assessed 4, 10 and 21 days post-immunization ( Figure 2A ).…”
Section: Resultsmentioning
confidence: 99%